Coordinated control for PV-ESS islanded microgrid without communication. (March 2022) - Su, Mei; Zhang, Kaizhe; Sun, Yao; Han, Hua; Shi, Guangze; Fu, Siqi
Highlights: A decentralized coordination control strategy is proposed for islanded PV-ESS microgrids with less ESS installation. Soft mode transition and constant value of PV-boost voltage are achieved. Small-signal stability, dynamic and steady state performances of the system are analyzed in theory and simulation. Abstract: Energy storage systems (ESSs) could help maintain real-time power balance of islanded microgrids, but they cost too much. In this paper we propose a coordinated control strategy without communication for an islanded microgrid, where less ESSs are installed. The microgrid is made up of photovoltaics (PVs) and ESSs inverters and loads. In the proposed method, PVs can achieve both MPPT operation and frequency regulation by using adaptive frequency droop. In the meanwhile, PVs can curtail the output power and switch to proportional droop to support the microgrid when ESSs are insufficient to absorb the surplus power. For ESSs, the droop control is adopted for grid-supporting ability until the limit of charging power is activated by the power limit controller. Generally, the control strategy for each unit is able to softly and autonomously switch to the proper mode based on the state of charge (SOC) of ESSs, the total load demand and the frequency level in the microgrid. Besides, the control strategy can coordinate the AC microgrid with arbitrary PVs and ESSs. Furthermore, the small-signal models of the microgrid in different modes are established to analyze the design of control coefficients. Finally, the proposed strategy is validated in Matlab/Simulink simulation and hardware-in-loop (HIL) tests under different cases.